A retrospective cohort study to find out the association of hydroxychloroquine prophylaxis and COVID 19 infection prevention among health care workers in a tertiary care hospital of New Delhi - Mathur, Neeraj Narayan; Arora, Shweta; Rasania, Sanjeev Kumar; Jais, Manoj Bharatlal; Talukdar, Tanmaya (Indian Journal of Community Health, 2021)
Background- With the high morbidity and mortality year 2020 will be remembered as Covid19 pandemic year. Occupational exposure to COVID 19 among health care workers poses a major risk to their lives. Hydroxychloroquine (HCQ) prophylaxis has been indicated for their use without much scientific evidence. Objective- to find if HCQ prophylaxis had association with Covid19 infection prevention among health care workers. Material &Method- A retrospective cohort study was conducted; through online by utilizing social media platform, among Health care workers of a tertiary care hospital from 1st June 2020 to 27 July 2020. Those HCWs who have taken HCQ (exposed) and who have not taken (nonexposed) and PCR tested Covid19 Positive were taken as diseased. Results Out of 527 who were analyzed, study subjects who took HCQ prophylaxis had 30% less chance of having Covid19 test positive, {RR- 0.709(0.383-1.296)} as compared those who didn’t took it, but the results were not significant. Conclusion- Hydroxychloroquine prophylaxis does not prevent Covid 19 infection and more evidence may be required for use of HCQ prophylaxis for Covid19 infection. Keywords- Hydroxychloroquine prophylaxis, Covid19 infection, Health care workers, Retrospective cohort study